Feasibility of Computer‐Based Self‐Administered Cancer‐Specific Geriatric Assessment in Older Patients With Gastrointestinal Malignancy. (3rd January 2013) - McCleary, Nadine J.; Wigler, Devin; Berry, Donna; Sato, Kaori; Abrams, Thomas; Chan, Jennifer; Enzinger, Peter; Ng, Kimmie; Wolpin, Brian; Schrag, Deborah; Fuchs, Charles S.; Hurria, Arti; et al.
Abstract : Background: The Cancer‐Specific Geriatric Assessment (CSGA) is a primarily self‐administered paper survey of validated measures. Methods: We developed and tested the feasibility of a computer‐based CSGA in patients ≥70 years of age who were receiving treatment for gastrointestinal malignancies at the Dana‐Farber Cancer Institute. From December 2009 to June 2011, patients were invited to complete the CSGA at baseline (start of new treatment) and follow‐up (at the first of 4 months later or within 4 weeks of completing treatment). Feasibility endpoints were proportion of eligible patients consented, proportion completing CSGA at baseline and follow‐up, time to complete CSGA, and proportion of physicians reporting CSGA results that led to a change in clinical decision‐making. Results: Of the 49 eligible patients, 38 consented (76% were treatment naive). Median age was 77 years (range: 70–89 years), and 48% were diagnosed with colorectal cancer. Mean physician‐rated Karnofsky Performance Status was 87.5 at baseline (SD 8.4) and 83.5 at follow‐up (SD 8). At baseline, 92% used a touchscreen computer; 97% completed the CSGA (51% independently). At follow‐up, all patients used a touchscreen computer; 71% completed the CSGA (41% independently). Mean time to completion was 23 minutes at baseline (SD 8.4) and 20 minutes at follow‐up (SD 5.1). The CSGA added information to clinical assessment for 75% at baseline ( n = 27) and 65% at follow‐up ( n = 17), but it did not alter immediate clinical decision‐making. Conclusion: The computer‐based CSGA feasibility endpoints were met, although approximately half of patients required assistance. The CSGA added information to clinical assessment but did not affect clinical decision‐making, possibly due to limited alternate treatment options in this subset of patients. Abstract : A computer‐based cancer specific geriatric assessment was developed and tested among patients age 70 and older receiving treatment for gastrointestinal malignancies at the Dana‐Farber Cancer Institute. The feasibility endpoints were met, although half of the sample required assistance and the results did not affect immediate clinical decision‐making. Abstract : 摘要 背景 . 癌症特异性老年评估（CSGA）是一种经过验证的、主要通过自填书面问卷的调查方法。 方法 . 我们在≥70岁的老年胃肠道恶性肿瘤患者中开展研究，并验证基于计算机的CSGA可行性，这些患者均在Dana‐Farber癌症中心接受治疗。2009年12月∼2011年6月，邀请上述患者在基线期（新治疗开始）和随访期（治疗4个月后或完成治疗的4周内）完成CSGA。可行性终点为知情同意的患者比例、基线期和随访期完成CSGA的比例、完成CSGA所需的时间、报告CSGA引起临床决策制定发生改变的医生比例。 结果 . 49例符合条件的患者中，38例知情同意（76%为初治患者）。中位年龄为77岁（范围：70∼89岁），48%确诊为结直肠癌。医生评定的Karnofsky体能状态平均评分在基线期为87.5（SD，8.4），在随访期为83.5（SD，8）。在基线期，92%的患者使用触摸屏电脑；97%完成CSGA（其中51%独立完成）。在随访期间，全部患者使用触摸屏电脑；71%完成CSGA（其中41%独立完成）。完成CSGA所需平均时间在基线期为23分钟（SD，8.4），在随访期为20分钟（SD，5.1）。CSGA在基线期提供的临床评估信息为75%（ n = 27），在随访期为65%（ n =17），但并未立即改变当时的临床决策制定。 结论 . 研究达到了基于计算机的CSGA可行性终点，近半数的患者需要协助完成。CSGA为临床评估提供了信息，但并未影响临床决策制定，可能归因于患者亚组中可替代的治疗选择比较有限。